Peningkatan Kapasitas Akademik: Pelatihan Analisis Hasil Penelitian dan Manajemen Referensi Berbasis Mendeley - da Costa, Romilda Arivina; Supriyono, Areni Yulitawati; Sarbuan, Defita; Amura, Putri Nurul Aien; Umkeketony, Sarleoki Nancy (Universitas Pattimura, 2025)
Efficient reference management and bibliography preparation are essential skills for students to support the quality of academic work. The Indonesian Language and Literature Education Study Program at Pattimura University (PBSI Unpatti) faces challenges related to reference management skills, particularly in using Mendeley software. The community service activity (PkM) was carried out on September 26–27, 2025. This activity was attended by 17 PBSI students from the 2019–2022 cohorts with the aim of improving students’ understanding, skills, and confidence in using Mendeley for research result analysis and academic writing. The training was conducted using a participatory, practice-based approach, including theory sessions, demonstrations of Mendeley usage, hands-on practice, and Q&A discussions. Evaluation results showed that the majority of participants experienced improvements in material comprehension, practical Mendeley skills, and confidence in using the software. These findings indicate that practice-based training is effective in enhancing students’ academic capacity, particularly in reference management and academic writing. The training also provides a foundation for the development of follow-up activities and the integration of digital literacy into the PBSI Unpatti curriculum.